Bincarung: Children’s Kawih Compositions Based on Sundanese Local Wisdom - Saiful, Abizar Algifari; Sukmayadi, Yudi; Masunah, Juju (Malaysian Journal of Music, 2025)
Bincarung is a collection of children’s songs by Koko Koswara and M. O. Koesman. Both prominent Sundanese figures of their time, Koswara (or Mang Koko) is recognised as a key musical reformer, whereas Koesman is known for his work as an educator. The collection is intended for children in elementary school, specifically those in grades one to four. Each song is paired with a play activity and reflects both musical considerations and the verbal and physical elements involved in that activity. In composing the songs, Mang Koko and Koesman took into account the children’s developmental stage alongside the nature of the accompanying games. This attentiveness lends the repertoire a distinctive identity. The present study examines the musical composition of the songs included in Bincarung. A qualitative research design using a case study approach was employed. Data were gathered through interviews, a review of relevant literature, and an analysis of the Bincarung manuscript, including comparison of its notated material with existing cassette recordings. The study identifies several musical traits that characterise the collection, all shaped by pedagogical aims. These include: 1) vocal ranges appropriate for children; 2) the use of the salendro tuning system, which conveys a sense of happiness, cheerfulness, and liveliness; and 3) predominantly stepwise melodic motion, for example, tone da (1) to tone mi (2) and tone ti (4) to tone na (3).